Effect of Stocking Density on the Growth, Survival, and Behavior of Postpuerulus Western Rock Lobster, Panulirus cygnus (George) (Decapoda: Palinuridae) - Moyle, K.; Johnston, D.; Knott, B.; Smith, Roy; Walker, D. (World Aquaculture Society, 2009)
The effect of four stocking densities (30, 60, 100, and 150 lobsters/m2) on the growth and survival of Panulirus cygnus postpueruli was determined over a 112-d grow-out trial. Agonistic behavior at each experimental density was recorded using infrared filming. Survival and growth decreased with increasing density, although this trend was only significant between the lowest (30/m2) and the highest densities (150/m2) (P < 0.05) at the conclusion of the grow-out trial. Density had no significant effect on apparent feed intake but significantly affected food conversion ratios (FCR) across all four densities, with FCR being best at 30/m2 and worst at 150/m2. The number and frequency of agonistic encounters per tank differed significantly with density, with agonistic encounters being highest at 150/m2 and lowest at 30/m2. Agonistic encounters coincided with the crepuscular foraging pattern of postpueruli. The reduction in survival and growth of postpueruli at the highest density (150/m2) can be attributed to the significant increase in the number of agonistic encounters. This study supports that P. cygnus postpueruli should be stocked at densities less than 100/m2 in order to minimize the negative effect of density on growth and survival.